Straits Settlements Blue Book (imports/exports) 1916-1917 vol. 66-67 (Great Britain : Public Record Office, 1971)
Mengandungi sambungan'Straits Settlements return of imports and exports during the year 1916';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other countries in 1915 and 1916, 1916 and 1917';'Return of imports and exports for the year 1917';'Blue Book for the year 1917'.